Expansion of the Clavulanic Acid Gene Cluster: Identification and In Vivo Functional Analysis of Three New Genes Required for Biosynthesis of Clavulanic Acid by Streptomyces clavuligerus - Li, Rongfeng (American Society for Microbiology, 2000)
Clavulanic acid is a potent inhibitor of β-lactamase enzymes and is of demonstrated value in the treatment of infections by β-lactam-resistant bacteria. Previously, it was thought that eight contiguous genes within the genome of the producing strain Streptomyces clavuligerus were sufficient for clavulanic acid biosynthesis, because they allowed production of the antibiotic in a heterologous host (K. A. Aidoo, A. S. Paradkar, D. C. Alexander, and S. E. Jensen, p. 219–236, In V. P. Gullo et al., ed., Development in industrial microbiology series, 1993). In contrast, we report the identification of three new genes, orf10 (cyp), orf11 (fd), and orf12, that are required for clavulanic acid biosynthesis as indicated by gene replacement and trans-complementation analysis in S. clavuligerus. These genes are contained within a 3.4-kb DNA fragment located directly downstream of orf9 (cad) in the clavulanic acid cluster. While the orf10 (cyp) and orf11 (fd) proteins show homologies to other known CYP-150 cytochrome P-450 and [3Fe-4S] ferredoxin enzymes and may be responsible for an oxidative reaction late in the pathway, the protein encoded by orf12 shows no significant similarity to any known protein. The results of this study extend the biosynthetic gene cluster for clavulanic acid and attest to the importance of analyzing biosynthetic genes in the context of their natural host. Potential functional roles for these proteins are proposed.